Species of Wadicosa (Araneae, Lycosidae): a new species close to W. quadrifera (Gravely) from the Western Ghats, India - Kronestedt, Torbjörn (Zootaxa, 2017)
The wolf spider species Wadicosa ghatica sp. nov. is described on material of both sexes from the states of Karnataka and Kerala in India. The species is morphologically close to W. quadrifera (Gravely, 1924), a widespread species from Sri Lanka and southern India. For comparison, the copulatory organs of both species are illustrated in detail. The males of both species are characterized by a corkscrew-like embolus which exhibits species-specificity in details of configuration. The embolus shape is unique to these two species.